Effect of Different Plant Growth Regulators on Somatic Embryogenesis Induction from Immature Female Inflorescences of Date palm cv. Bronsi - Milad, Khalifa M.; Ben hamida, Abdusaalam; bensaad, Zuher (Al-Mukhtar Journal of Sciences, 2023)
A study was conducted to determine the effect of different growth regulators on somatic embryogenesis induction and micropropagation of date palm cv. Bronsi. using immature female inflorescence. Unopened spathes were collected, flower strands removed, and surface sterilized by using commercial sodium hypochlorite solution Clorox ( 1.05%), then flowers were cultured onto full strength MS medium supplemented with various concentrations of 2,4-D, IBA, Kinetin (Kin), and isopentenyl adenine (2ip) and incubated in the dark at 27℃ for four months. Some plant explants showed a response in embryogenic callus formation, which were then subcultured on MS growth regulators-free media with the addition of 0.5 mg.L-1 GA3. The highest number of growing shoots and shoot length were obtained from somatic embryos developed on 2ip (0.2) +Kin (0.2) +IBA (0.5) + GA3 (0.5) containing medium. To encourage root growth and elongation, embryos were transferred to an MS medium provided with NAA at concentrations of 0.1, 0.5, and 1.0 with the addition of BA at 0.2 mg.L-1. Using NAA (0.1) with BA (0, 2) achieved the highest number of roots per plant (8.0) and root length (10.4 cm).